2018
DOI: 10.1186/s40623-018-0902-9
|View full text |Cite
|
Sign up to set email alerts
|

VHF radar measurements of momentum flux using summer polar mesopause echoes

Abstract: We revisit previously unpublished analysis of observations of the dynamics of the mesopause region over the Norwegian Island of Andøya (69°N, 16°E) made during a 1-week period in summer 1987 during the Middle Atmosphere Cooperation-Summer in Northern Europe (MAC-SINE) campaign using the mobile SOUSY VHF (53.5 MHz) Doppler radar operating in a six-beam mode. We do this in the light of: (1) more recent developments in the measurement of the components of the density-normalized Reynolds stress tensor using meteor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…However, particle precipitation still affects PMSE when they both occur simultaneously. Reid et al (2018a) used PMSE echo data for the measurement of momentum flux and found reasonable results compared to previous studies with meteor radars and medium frequency (MF) radars. Belova et al (2018) conducted a case study of polar mesospheric winter echoes (PMWE) using the tristatic EISCAT radar.…”
Section: Study Of Polar Mesospheric Echoessupporting
confidence: 54%
“…However, particle precipitation still affects PMSE when they both occur simultaneously. Reid et al (2018a) used PMSE echo data for the measurement of momentum flux and found reasonable results compared to previous studies with meteor radars and medium frequency (MF) radars. Belova et al (2018) conducted a case study of polar mesospheric winter echoes (PMWE) using the tristatic EISCAT radar.…”
Section: Study Of Polar Mesospheric Echoessupporting
confidence: 54%
“…θ E in Eq. ( 2) is the effective beam direction for the off-zenith beams, which should replace the apparent off-vertical angle θ A considering the influence of aspect sensitivity (Reid et al, 2018b).…”
Section: Gravity Wave Momentum Flux and Vertical Transport In The Tro...mentioning
confidence: 99%
“…Here 𝑣 𝐸 , 𝑣 𝑊 , 𝑣 𝑁 , 𝑣 𝑆 represent the radial perturbation velocities in the east, west, north, south beams, and 𝑢 ′ , 𝑣 ′ , 𝑤 ′ refer to the fluctuating zonal, meridional, vertical winds, respectively. 𝜃 𝐸 in equation ( 2) is the effective beam direction for the off-zenith beams, which should replace the apparent off-vertical angle 𝜃 𝐴 considering the influence of aspect sensitivity (Reid et al, 2018b). As we have seen above, the mean winds evaluated assuming that the apparent and effective beam angles are the same are in excellent agreement with the radiosonde measurements in the present study, and with numerous other intercomparisons made with this ST radar type.…”
Section: Gravity Wave Momentum Flux and Vertical Transport In The Tro...mentioning
confidence: 99%